ab(a-b)平方-a(b-a)立方 分解因式
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 17:14:02
ab(a-b)平方-a(b-a)立方分解因式ab(a-b)平方-a(b-a)立方分解因式ab(a-b)平方-a(b-a)立方分解因式ab(a-b)平方-a(b-a)立方=ab(a-b)平方+a(a-b
ab(a-b)平方-a(b-a)立方 分解因式
ab(a-b)平方-a(b-a)立方 分解因式
ab(a-b)平方-a(b-a)立方 分解因式
ab(a-b)平方-a(b-a)立方
=ab(a-b)平方+a(a-b)立方
=a(a-b)^2(b+a-b)
=a^2(a-b)^2
(a-b)^2(ab+a^2-ab)=a^2(a-b)^2
因式分解:a立方+a平方b-ab平方-b立方
a平方b`(ab立方)平方
ab(a-b)平方-a(b-a)立方 分解因式
a立方b-ab立方
a立方-2a平方b+ab平方
-3a立方+6a平方b-3ab平方
ab平方-2a平方b+a立方
一a立方+2a平方b—ab平方
-a平方b(a立方b平方-3a平方b+b立方)-2ab平方(a4次方b-3a立方-2ab平方)
分解因式:a平方b-2ab平方+b立方
-(2ab)立方+3ab×a平方b平方
8a立方b平方-12ab平立方c
(ab-b的平方)除以a+b分之a的立方b-ab的立方
a平方+ab=3,a平方-ab=5,则a平方-a立方b
【12(a平方b)立方b平方+3a平方(3a平方b立方-ab平方)】➗(3a立方b平方)
因式分解 a的立方-ab的平方-a+b
6a立方b平方-4a立方b平方-8ab四次方 因式分解
分解因式a的立方b-2a的平方b的平方+ab的立方